Learning and Teaching for the Twenty-First Century
XXIV, 324 p.
Keywords: This book stresses learning and teaching, rather than teaching and learning. The contention of the contributors is that the focus in all educational endeavours should not be primarily on teachers and teaching, but on learners; how to best facilitate learning, in the most effective, enjoyable, relevant and cost-effective ways for learners, whether they be children, youth or adults. The focus is therefore on how learning can be enhanced, through effective teaching; and how individuals can be best prepared to be excellent teachers. This ground-breaking book examines the personal dimensions of learning and teaching, and various aspects of education reform. It particularly focuses on the situation in the Asia-Pacific region, yet draws on best and innovative practices from the international arena. The book brings together the thoughts and insights offered by international leaders in the fields of teaching and learning. It seeks to build a bridge between researchers, policy makers and practitioners.